AI-in-the-making in strategy work : A sociomaterial study of human-GenAI strategizing in SMEs - Pyrhönen, Julius (My University, 2026)
Technological advancements are constantly offering new opportunities to transform routines at work and in leisure time, and companies are turning to technology to streamline their operations and gain a competitive edge. There is widespread discussion about the use of generative AI in companies, but there is still limited experience with its applications, particularly in strategy work. This study examines ways to utilize generative AI in Finnish small and medium-sized enterprises through a qualitative case study. The aim is to investigate how collaboration between humans and generative AI can improve creativity and the quality of decision-making in strategizing. The study draws on theories of sociomateriality and discursivity, as well as the nature of human-AI interaction, to form the theoretical framework for this research. Generative AI has only been on the market for a few years, so there is still limited data and experience regarding its use in strategy work, particularly in small and medium-sized enterprises. This study contributes to the research literature by examining the use of AI from a practical perspective in four Finnish companies. The research data consists of interviews with company representatives, and the perspective was further expanded through interviews with strategy consultants. The research shows that generative AI is a versatile tool for developing strategic thinking, accelerating and facilitating the strategy process, and defining a company’s strategic direction. The adoption of AI in strategy work significantly impacts the nature of the work and requires new practices, skills, and hands-on effort. The development of a strategy tool is a company-specific, individualized process, whose starting points and directions are linked to the historical, cultural, and worldview factors of the company, its employees, and the technology. The sociomaterial context presents each company with unique barriers and drivers for developing a strategy tool, but the research results show that employees’ curious attitude and willingness to learn collaboratively through practical experimentation can lead to the development of strategy work through strengthened reflection, the mapping of expanded strategic opportunities, and the development of new strategy tools. Human creativity and the ability to create meaning, facilitated by generative AI, remain a key quality factor in strategic work, even in SMEs. Consequently, practices that support learning and reduce the emotional and cognitive strain caused by new strategizing context are essential for successful tool development.

Teknologinen kehitys tarjoaa jatkuvasti uusia mahdollisuuksia muuttaa rutiineja työssä ja vapaa-ajalla, ja yritykset hakevat teknologiasta mahdollisuuksia tehostaa toimintaa ja hakea kilpailuetua. Generatiivisen tekoälyn käytöstä yrityksissä puhutaan laajasti, mutta sen käytöstä on vielä niukasti kokemusta etenkin strategiatyössä. Tämä tutkimus tarkastelee tapoja hyödyntää generatiivista tekoälyä suomalaisissa pienissä ja keskisuurissa yrityksissä laadullisella tapaustutkimuksella. Tavoitteena on selvittää kuinka ihmisen ja generatiivisen tekoälyn yhteistyöllä voidaan parantaa luovuutta ja päätöksenteon laatua strategiatyössä. Tutkimus hyödyntää teorioita sosiomateriaalisuudesta ja diskursiivisuudesta, sekä ihmisen ja tekoälyn vuorovaikutuksen luonteesta pohjana tämän tutkimuksen teoreettiselle viitekehykselle. Generatiivinen tekoäly on ollut markkinoilla vasta muutaman vuoden, joten tutkimusaineistoa ja kokemuksia sen hyödyntämisestä strategiatyössä varsinkin pk-yrityksissä on vielä rajallisesti. Tämä tutkimus täydentää tutkimuskirjallisuutta käsittelemällä tekoälyn käyttöä käytännön näkökulmasta neljässä suomalaisessa yrityksessä. Tutkimusaineistona käytetään yritysten edustajien haastatteluita, ja lisäksi näkökulmaa laajennettiin kahden strategiakonsultin haastatteluilla. Tulokset osoittavat että generatiivinen tekoäly on monipuolinen työkalu strategisen ajattelun kehittämiseen, strategiaprosessin nopeuttamiseen ja fasilitointiin, sekä yrityksen strategisen suunnan määrittämiseen. Tekoälyn käyttöönotto strategiatyössä vaikuttaa työn luonteeseen huomattavasti, ja vaatii uusia käytäntöjä, taitoja, ja käytännön työtä. Strategiatyökalun kehittäminen on yrityskohtainen, yksilöllinen prosessi, jonka lähtökohdat ja kehityssuunnat ovat sidoksissa yrityksen, työntekijöiden ja teknologian historiallisiin, kulttuurisiin, ja maailmankuvallisiin tekijöihin. Sosiomateriaalinen kokonaisuus tuo jokaiseen yritykseen yksilölliset esteet ja ajurit strategiatyökalun kehittämiseen, mutta tutkimuksen tulokset osoittavat että työntekijöiden utelias asenne ja halu oppia yhteisöllisesti käytännön kokeilun kautta voivat johtaa strategiatyön kehittymiseen vahvistuvan reflektion, laajentuneiden strategisten mahdollisuuksien kartoittamisen, ja uusien strategiatyökalujen kehittämisen myötä. Ihmisten luovuus ja kyky luoda merkityksiä generatiivisen tekoälyn fasilitoimana on yhä keskeinen laatutekijä strategiatyössä myös pk-yrityksissä. Siitä johtuen käytännöt joilla tuetaan uuden oppimista ja vähennetään uuden tilanteen aiheuttamaa emotionaalista ja kognitiivista rasitusta ovat olennaisia onnistuneelle työkalunrakennukselle.
Keywords: small and medium-sized enterprises; strategies; leadership (activity); enterprises; strategic leadership; corporate strategies; organisations (systems); strategic planning; development (active); self-evaluation; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development